Acute stress induces an inflammation dominated by innate immunity represented by neutrophils in mice - Tang, Lanjing; Cai, Nannan; Zhou, Yao; Liu, Yi; Hu, Jingxia; Li, Yalin; Yi, Shuying; Song, Wengang; Kang, Li; He, Hao (Frontiers in Immunology, 2022)
It is well known that psychological stress could affect the immune system and then regulate the disease process. Previous studies mostly focused on the effects of chronic stress on diseases and immune cells. How acute stress affects the immune system remains poorly understood. In this study, after 6 hours of restraint stress or no stress, RNA was extracted from mouse peripheral blood followed by sequencing. Through bioinformatics analysis, we found that when compared with the control group, differentially expressed genes in the stress group mainly displayed up-regulated expression. Gene set enrichment analysis results showed that the enriched gene terms were mainly related to inflammatory response, defense response, wounding response, wound healing, complement activation and pro-inflammatory cytokine production. In terms of cell activation, differentiation and chemotaxis, the enriched gene terms were related to a variety of immune cells, among which neutrophils seemed more active in stress response. The results of gene set variation analysis showed that under acute stress, the inflammatory reaction dominated by innate immunity was forming. Additionally, the concentration of serum IL-1β and IL-6 increased significantly after acute stress, indicating that the body was in an inflammatory state. Importantly, we found that acute stress led to a significant increase in the number of neutrophils in peripheral blood, while the number of T cells and B cells decreased significantly through flow cytometric analysis. Through protein-protein interaction network analysis, we screened 10 hub genes, which mainly related to inflammation and neutrophils. We also found acute stress led to an up-regulation of Ccr1, Ccr2, Xcr1 and Cxcr2 genes, which were involved in cell migration and chemotaxis. Our data suggested that immune cells were ready to infiltrate into tissues in emergency through blood vessels under acute stress. This hypothesis was supported in LPS-induced acute inflammatory models. After 48 hours of LPS treatment, flow cytometric analysis showed that the lungs of mice with acute stress were characterized by increased neutrophil infiltration, decreased T cell and B cell infiltration. Immunohistochemical analysis also showed that acute stress led to more severe lung inflammation. If mice received repeat acute stress and LPS stimulation, the survival rate was significantly lower than that of mice only stimulated by LPS. Altogether, acute stress led to rapid mobilization of the immune system, and the body presented an inflammatory state dominated by innate immune response represented by neutrophils.